Методика расчета мощности электроприводов манипуляторов обжимных прокатных станов - Коцюбинский, Виктор Семенович; Пипкин, Ю. В.; Коцюбинская, Н. В.; Тарик, Мухаммад (НТУ "ХПИ", 2010)
The problem of the calculation to powers of the electric motors on given maximum importance's of the velocity and at most possible time of the working the mechanism with provision for possible heat mode is solved for the first time in article. The broughted methods of the choice to powers is recommended for use when designing electricdrive auxiliary mechanism of the rolling mills, as well as the main electricdrive up down figure of the hot rolling.
Methodic of the calculation power of the electric motors from rolling mill manipulator
Keywords: линейка стальная; рейка зубчатая; штанга; электродвигатель; сопротивление статическое; блюминг